The technical expert/clinical user/patient panel (TECUPP): centering patient and family perspectives in patient-reported measure development - Elizabeth Marsolais; Rebecca Anhang Price; Carl T. Berdahl; Anton Shenk; Lucy Schulson; Claire E. O’Hanlon (Research Involvement and Engagement)
Abstract Patient and caregiver perspectives are increasingly incorporated into health care research and policymaking, but their inclusion in the quality measure development process often is not robust. We describe a stakeholder panel model for incorporating patient/caregiver voices in the development of patient-reported measures, the Technical Expert/Clinical User/Patient Panel (TECUPP) model. This model is characterized by significant or equal representation of people with lived experience of the disease or condition (as patients or caregivers) to the clinicians and others with technical expertise who typically comprise technical expert panels. We report key design features of the TECUPP model and how we used this model to develop survey-based patient experience measures of timeliness of cancer diagnosis. We describe benefits and challenges of using the TECUPP model and considerations to guide others who might use it as part of developing patient-centered quality measures, based on our experience convening a TECUPP to inform development of a patient-reported measure on timeliness of cancer diagnosis. Benefits include creating space for significant contributions from patients/caregivers and development of a shared understanding of patient experiences and observability of measure domains between clinicians and patients/caregivers. Challenges include time management and managing conversations outside the project scope. Measure development efforts implementing this model should consider recruiting diverse individuals, scheduling short and frequent meetings, enabling participation from all TECUPP members, developing accessible pre-read materials, anchoring meetings with patient stories, and encouraging multiple communication modes. The TECUPP model promotes discussion and understanding by patients/caregivers and clinicians/measure experts helpful for development of survey-based patient-reported measures.